Implementasi Pendidikan Ramah Lingkungan Dalam Membentuk Karakter Siswa Di SMPN 1 Darul Aman Kabupaten Aceh Timur - Fahlevi, Agamsyah; Asrul (Program Studi Pendidikan Agama Islam, 2024)
The purpose of this study is to describe the design, implementation, evaluation and follow-up of the implementation of environmentally friendly education in the formation of children's character and to explain the implementation model of environmentally friendly education in the formation of children's character at SMPN 1 Darul Aman. Then the method that the author uses uses a descriptive qualitative approach with the type of analysis descriptive research then in collecting data the authors use the instrument of observation, interviews and documentation. The results of this study include planning for environmentally friendly education programs in shaping the character of children at SMPN 1 Darul Aman starting with the formation of a school team, preparing a school environmental study, and preparing an environmental action plan that aims to shape the character of environmental care in students. The implementation of the program begins by providing socialization to all school residents guided by the implementation of environmentally sound policies, implementation of an environment-based curriculum, and the implementation of environmental activities. In addition, the implementation of the program is pursued through a habituation approach that creates habits or behavior for all school members in terms of automatic environmental care and maintenance and continues. Evaluation of environmentally friendly education programs in the formation of children's character at SMPN 1 Darul Aman can be seen from the attitudes and behavior of all school members in daily activities that have been carried out properly according to standards and plans that have been prepared and various programs so as to foster attitudes and daily behavior of residents the school has reflected the behavior of caring for the environment. Then the model or form of implementing environmentally friendly education in shaping the character of children at SMPN 1 Darul Aman is implemented in the form of active participation by all school members and has been going well and has provided benefits to school residents by creating a generation that cares about the environment. With this environmentally friendly education program, it is also hoped that students will be able to apply environmental care behavior in everyday life wherever they are as a form of embodiment of character or caring attitude towards the environment. Keywords: Implementation, Education, Environmentally Friendly